A Rare Case of Septic Arthritis of Lumbar Facet Joint with Epidural Abscess, and Bacterial Meningitis Caused by Methicillin-Sensitive Staphylococcus aureus - Maldonado-Morán, Miguel; Muñoz, Juan M.; Matta, Javier I.; Arrieta, Victor M.; Bernal, Oscar P.; Mejía, Jairo M. (Indian Journal of Neurosurgery, 2018)
Septic arthritis of the facet joint is an extremely rare condition, even more in young immunocompetent patients. There have been approximately only 40 cases of this entity reported worldwide. Here, the authors present a 16-year-old male patient with lower back pain, fever, and cephalea. Blood cultures and cerebrospinal fluid analysis confirmed methicillin-sensitive Staphylococcus aureus infection, and magnetic resonance imaging showed septic arthritis of the lumbar left facet joint L3 and epidural abscess. Intravenous oxacillin was administered, and the patient improved. No other treatment was required.
Keywords: septic arthritis; facet joint; epidural abscess; meningitis; Staphylococcus aureus